ANALISIS FLUKTUASI NILAI TUKAR RUPIAH/USD PADA PERAN UANG BEREDAR DAN SUKU BUNGA DALAM KEGIATAN IMPOR DI INDONESIA - Manihuruk, Frido Evindey; Siregar, Rahel Veronika; Silaban, Putri Sari Margaret Julianty; Feby, Yohana; Gultom, Rona Hinirim; Irsyad, Ferozi Ramdana (Politeknik Bisnis Indonesia, 2024)
Fluctuations in the Rupiah exchange rate against the US Dollar currently tend to weaken in the long run, which is thought to be caused by excessive import activity. The existence of the Money Supply (JUB) and the Interest Rate which is a monetary policy conducted by Bank Indonesia and is thought to have a major influence on the Rupiah / USD exchange rate. This study aims to determine how much the money supply and interest rates affect the Rupiah exchange rate against the US Dollar through import activities in Indonesia from 2004-2023. This qualitative research uses secondary data (times series) from BPS Indonesia publications, then analyzed using multiple linear regression analysis and path analysis, which has previously been confirmed to be free from classical assumption tests. The results show that JUB has a positive and significant effect on import activity. However, the interest rate, proxied by the BI rate, has little impact on imports. Indirectly, JUB has a significant effect on Rupiah exchange rate through imports, but this is not in line with the effect of interest rate. The results of the analysis suggest that monetary authorities should pay attention to JUB and interest rates in conducting import activities carried out by the government in order to maintain the stability of the Rupiah/US exchange rate and create a good level of economic growth.